Representasi Nilai-nilai Budaya Batak pada Film Ngeri Ngeri Sedap - Nasution, M. Djanji Akbar (Multiverse: Open Multidisciplinary Journal, 2024)
This study aims to analyze the representation of Batak cultural values in the film "Ngeri Ngeri Sedap." The research background emphasizes the importance of films as a medium for conveying and preserving cultural values for younger generations. The research questions focus on how Batak cultural values are represented in this film and to what extent the film successfully communicates these cultural messages. The research employs a qualitative analysis with a case study approach, collecting data through observations, interviews, and literature review. The findings reveal that the film effectively represents Batak cultural values, such as mutual cooperation, respect for elders, and the importance of maintaining traditions. The conclusion drawn is that "Ngeri Ngeri Sedap" not only entertains but also effectively conveys and preserves Batak cultural values to its audience. This film serves as an important reference for cultural preservation efforts through visual media.